2015
DOI: 10.1016/j.jcyt.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone regeneration potential of dental follicle stem cells for treatment of craniofacial defects

Abstract: Stem cell-based tissue regeneration offers potential for treatment of craniofacial bone defects. The dental follicle (DF), a loose connective tissue surrounding unerupted tooth, has been shown to contain progenitor/stem cells. Dental follicle stem cells (DFSCs) possess strong osteogenesis capability, which makes them suitable for repairing skeletal defects. The objective of this study was to evaluate bone regeneration capability of DFSCs loaded into polycaprolactone (PCL) scaffold for treatment of craniofacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…ZnO was combined with PCL which allowed for the slow release of zinc. PCL has been investigated widely for tissue engineering cartilage and bone (Rezai‐Rad et al, ; Wise, Yarin, Megaridis, & Cho, ; Xue et al, ). With the addition of ZnO to PCL, the chondrogenic differentiation was enhanced where cells on the low percentage of ZnO demonstrated increased GAG and collagen type II production and gene expression of chondrogenic markers.…”
Section: Discussionmentioning
confidence: 99%
“…ZnO was combined with PCL which allowed for the slow release of zinc. PCL has been investigated widely for tissue engineering cartilage and bone (Rezai‐Rad et al, ; Wise, Yarin, Megaridis, & Cho, ; Xue et al, ). With the addition of ZnO to PCL, the chondrogenic differentiation was enhanced where cells on the low percentage of ZnO demonstrated increased GAG and collagen type II production and gene expression of chondrogenic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were resuspend in medium containing DMEM (Life Technologies, Carlsbad, CA, United States), 20% fetal bovine serum (FBS) (Invitrogen, Carlsbad, CA, United States) + 1% Penicillin-Streptomycin 10,000 u/ml (Life Technologies, Carlsbad, CA, United States). This medium has been used previously as a growth medium for dental stem cells [23]. Cell suspension was immediately plated in a T-25 flask and placed at 37 C and 5% CO 2 , and non-adherent cells were removed by medium change a day after.…”
Section: Culturing Human Dpscs (Hdpscs)mentioning
confidence: 99%
“…Another study showed that ODAM cooperates with RUNX2 to modulate mineralization (Lee et al, 2010). Studies in our lab also revealed that rat DFSCs cultured in osteogenic medium dramatically and significantly increase the expression of osteogenic marker genes, osteocalcin and bone sialoprotein (Rezai Rad et al, 2015), suggesting that DFSCs can differentiate into osteoblasts under the proper conditions. In this study, we mimicked the increase of ODAM expression by transfecting the plasmid containing rat ODAM coding sequence into human and rat DFSCs, and found that increase of ODAM expression enhanced osteogenesis of the DFSCs at an early stage of osteo-induction when the transfected DFSCs were cultured in osteogenesis medium.…”
Section: Discussionmentioning
confidence: 81%